Selection of GAAP or RAP in the Savings and Loan Industry - Hill, John W.; Ingram, Robert W. (The Accounting Review, 1989)
[This study examines the choice of a regulatory accounting principle (RAP) in contrast to generally accepted accounting principles (GAAP) with respect to loan loss recognition in the savings and loan industry. RAP was permitted by the Federal Home Loan Bank Board for Savings and Loans (S&Ls) in the early 1980s. Many S&Ls selected this alternative to GAAP. We examine four factors, conditioned by accounting regulations in the S&L industry setting, hypothesized to explain the accounting choice. All of the factors are significant in logistic regression tests in which the choice of RAP or GAAP was the dependent variable. The results are consistent with the conclusion that S&Ls chose to violate GAAP when regulatory constraints induced a conflict between GAAP requirements and the economic welfare of the firm.]